The Fuzzy Prime Spectrum of Partially Ordered Sets - Derso Abeje Engidaw; Gezahagne Mulat Addis; Wondwosen Zemene Norahun; Dereje Kifle Boku; Habtu Bayafers Demrew; Tewodros Argachew Degefa (International Journal of Mathematics and Mathematical Sciences)
We study the space of prime fuzzy ideals (and the space of maximal fuzzy ideals as a subspace) equipped with the hull-kernel topology in partially ordered sets. Mainly, we investigate the conditions for which the fuzzy prime spectrum of a poset is compact, Hausdorff, and normal, respectively.